The Ambiguity of Norms Regarding the Limits of Authority of Radiology Specialists and Radiology Technical Personnel from the Perspective of Health Administration Law - Yuki Mulyani; Zudan Arief Fakrulloh (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2026)
This study aims to analyze the unclear norms regarding the boundaries of authority of radiologists and radiology technicians in the Indonesian health legal system and to formulate a normative reconstruction model based on the principles of legal certainty and administrative accountability. The problem arises because although Law Number 29 of 2004 concerning Medical Practice has attributed the authority to enforce diagnoses to physicians, and Law Number 17 of 2023 concerning Health regulates the position of health workers based on competence and licensing, there is no clear formulation regarding the operational boundaries between diagnostic authority and radiology technical authority. This condition creates unclear norms, regulatory disharmony, and potential uncertainty of legal accountability in radiology services. This study employs a normative juridical method with a statutory and conceptual approach. The results show that the authority of radiology diagnostics is an attributive authority inherent in radiology specialists, while the authority of radiology technicians is technical, operational, and administrative in nature and must be within the framework of medical supervision. The resulting vague norms contradict the principles of legality and legal certainty in state administrative law. Therefore, it is necessary to reconstruct the boundaries of authority through regulatory harmonization, the formulation of restrictive norms, and the strengthening of administrative oversight to ensure patient protection and professional accountability within the national health law system.